Microenvironmental Control of Adipocyte Fate and Function. Issue 10 (October 2016) - Pope, Benjamin D.; Warren, Curtis R.; Parker, Kevin Kit; Cowan, Chad A.
Abstract : The properties of tissue-specific microenvironments vary widely in the human body and demonstrably influence the structure and function of many cell types. Adipocytes are no exception, responding to cues in specialized niches to perform vital metabolic and endocrine functions. The adipose microenvironment is remodeled during tissue expansion to maintain the structural and functional integrity of the tissue and disrupted remodeling in obesity contributes to the progression of metabolic syndrome, breast cancer, and other malignancies. The increasing incidence of these obesity-related diseases and the recent focus on improved in vitro models of human tissue biology underscore growing interest in the regulatory role of adipocyte microenvironments in health and disease. Trends: Subcutaneous and visceral adipose depots are innervated, vascularized endocrine organs comprising multipotent progenitor cells and differentiated adipocytes. Brown adipocytes differ from white adipocytes in their morphology, functional capacities, and depot locations, but 'beige' or 'brite' adipocytes, which share characteristics of both white and brown adipocytes, are found in some white and brown depots. Adipocytes can expand several-thousand fold in size during cellular maturation and are electrically and metabolically coupled by gap junctions. Biophysical cues from the microenvironment modulate adipocyte differentiation, growth, and function. Altered adipocyte microenvironments in obesity are associated with type 2 diabetes mellitus, breast cancer, and other diseases, suggesting that microenvironmental factors in adipose tissue can be pathogenic.